Gulliver’s virtual travels: active embodiment in extreme body sizes for modulating our body representations - S. Serino; F. Scarpina; A. Chirico; A. Dakanalis; D. Di Lernia; D. Colombo; V. Catallo; E. Pedroli; G. Riva (Cognitive Processing, 2020)
It is noted that the perceptual experience of body and space can be modulated by changing the action capabilities or by manipulating the perceived body dimensions through a multisensory stimulation. This study adds to pre-existing literature by investigating the alterations in bodily experience following embodiment to both enlarged and shrunked bodies, while participants actively navigated in a virtual environment. A normal-sized body served as a reference condition. After each embodied navigation, participants estimated the height and width of three different body parts. Results revealed that the embodiment over shrunked body induced a significant reduction in participants’ body image, while no changes were reported after the embodiment over the enlarged body. Findings were discussed in terms of previous literature exploring the constraints implicated in the ownership over different bodies.